PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR KEPEWARAAN MAHASISWA PENDIDIKAN BAHASA INDONESIA DENGAN PEMBELAJARAN DARING - Putu Dessy Fridayanthi (Widyadari : Jurnal Pendidikan, 2021)
Online learning is learning that is done online using learning applications and social networks. Kepewaraan or emcee is a person in charge of leading and managing the course of an event. The purpose of this study was to determine the learning outcomes and student responses to the application of the discovery learning model in the civil service subject with online learning. This type of research is classroom action research which is implemented in an online form. The research subjects were students of the sixth semester of Indonesian and regional education at the University of PGRI Mahadewa Indonesia for the academic year 2020/2021. The object of research is the learning outcomes of the Civics subject with the application of discovery learning learning models with online learning. This study used two cycles, and each cycle went through four stages of the activity process (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. The data collection technique in this research is using the test and observation method. The results of the research show (1) The application of discovery learning learning models can improve the learning outcomes of civility subjects with online learning. (2) There is a positive response of students with online learning to the application of the discovery learning model.